EMENDED DESCRIPTION OF NEPENTHES SURIGAOENSIS (NEPENTHACEAE), A POORLY KNOWN SPECIES FROM MINDANAO (PHILIPPINES) - Lagunday, Noel E.; Amoroso, Victor B. (Phytotaxa, 2024)
An emended description of Nepenthes surigaoensis is provided herein. The species is grouped under section Insignes or N. ventricosa. It is easily delineated from N. merrilliana in having strongly decurrent leaf-to-stem attachment (N. merrilliana: obliquely decurrent up to 2/3rd of the stem internode), subcylindrical aerial pitchers (vs. wholly infundibular). The species is reported herein in Mt. Tago and Mt. Pantaron range and its adjacent mountains i.e. Mt. Kiamo, Barangay Kalabugao, and Barangay Eureka, Gingoog City, Misamis Oriental at 700 to 1100 m asl growing on gravel substrates along open ridges and on upper montane forests with clay-loam soils. The species is facing threats of poaching, shifting cultivation, without legislative protection and calls for conservation efforts.